2020
DOI: 10.1002/advs.202001882
|View full text |Cite
|
Sign up to set email alerts
|

Kilogram‐Scale Crystallogenesis of Halide Perovskites for Gamma‐Rays Dose Rate Measurements

Abstract: Gamma‐rays (γ‐rays), wherever present, e.g., in medicine, nuclear environment, or homeland security, due to their strong impact on biological matter, should be closely monitored. There is a need for simple, sensitive γ‐ray detectors at affordable prices. Here, it is shown that γ‐ray detectors based on crystals of methylammonium lead tribromide (MAPbBr3) ideally meet these requirements. Specifically, the γ‐rays incident on a MAPbBr3 crystal generates photocarriers with a high mobility‐lifetime product, allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…A perovskite-in-polymer membrane system showed negligible current reduction after a total dose of 376.8 Gy (equivalent to 1.88 million chest X-rays) 90 while MAPbBr 3 single crystals irradiated with a 230 Gy dose over 10 hours displayed no losses. 91 The retention of charge transport properties would suggest no significant material degradation, which is promising for scintillators.…”
Section: Pvk Scintillator Performancementioning
confidence: 99%
“…A perovskite-in-polymer membrane system showed negligible current reduction after a total dose of 376.8 Gy (equivalent to 1.88 million chest X-rays) 90 while MAPbBr 3 single crystals irradiated with a 230 Gy dose over 10 hours displayed no losses. 91 The retention of charge transport properties would suggest no significant material degradation, which is promising for scintillators.…”
Section: Pvk Scintillator Performancementioning
confidence: 99%
“…The MAPbBr 3 SCs used in the fabrication of the detector devices were grown using the inverse temperature crystallization method 20 . The SCs of a volume of 2 × 2 × 1 cm 3 were coated by graphite spray on two sides leaving a small gap in-between (6 mm).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the chemical formula of MAPbBr 3 contains elements of large atomic weight (high-Z), such as Pb and Br, thus leading to a high material density (~ 4 g cm −3 ), which is necessary for efficient impact ionization. Moreover, it has been shown that high-quality large MAPbBr 3 crystals, weighting even more than one kilogram, can be grown 20 . Such crystals are characterized by a unique correlation of relatively low trap concentration and high resistivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations